LITERATURE REVIEW : PENGARUH BIAS TERHADAP KEPUTUSAN INVESTOR DALAM BERINVESTASI SAHAM - Dennis Alexander Joedono; Evelyn (Universitas Widyatama, 2023)
Bias is a tendency for prediction errors (Shefrin, 2007). Investment decision bias is a deviation from the right and optimal decision making process because some investors do not study their own psychology (Halofina, 2021). This study aims to determine what biases are the most frequently studied and the most influential on stock investment decisions in Indonesia. The method used in this research is literature review. There are 50 studies published in the range of 2017 - 2022 that are reviewed in this study. The results showed that in general, the most frequently studied biases were overconfidence bias (significance 84%), herding bias (significance 65%), representativeness bias (56%). If devided by the age of the respondends, the biases that most frequently studied among young investors are herding bias (significance 50%), overconfidence bias (significance 83%) and regret aversion bias (significance 60%). Among student investors, the most frequently studied biases are overconfidence bias (significance 75%), herding bias (significance 63%), and representativeness bias (significance 80%). The results of this study are expected to be a reference for further research that discusses stock investment decision bias.